Perancangan Sistem Pakar Berbasis Web untuk Menentukan Kerusakan Komputer Menggunakan Metode Certainty Factor - Jaelani, Andry; Akbar , Rodi (Lembaga Publikasi Ilmiah Nusantara, 2025)
Computer device damage is often an obstacle for users, especially for those who do not have the technical knowledge to diagnose the problem. To overcome this problem, a system is needed that is able to provide an initial diagnosis quickly and accurately. This study aims to design and develop a web-based expert system that can help users determine the type of computer damage using the Certainty Factor (CF) method. The CF method is used to calculate the level of certainty of the symptoms entered by the user based on previously formulated expert knowledge. This system is built using the PHP programming language and MySQL database, and is designed to be widely accessible via the internet network. The test results show that the system is able to provide diagnostic results with an adequate level of accuracy and is close to the results of direct analysis by technicians. Thus, this system can be an effective tool in the process of identifying computer damage and providing initial recommendations for handling before users take the device to a professional technician.